2019
DOI: 10.1186/s12967-019-1898-z
|View full text |Cite
|
Sign up to set email alerts
|

Values of integration between lipidomics and clinical phenomes in patients with acute lung infection, pulmonary embolism, or acute exacerbation of chronic pulmonary diseases: a preliminary study

Abstract: Background The morbidity and mortality of patients with critical illnesses remain high in pulmonary critical care units and a poorly understood correlation between alterations of lipid elements and clinical phenomes remain unelucidated. Methods In the present study, we investigated plasma lipidomic profiles of 30 patients with severe acute pneumonia (SAP), acute pulmonary embolism (APE), and acute exacerbation of chronic pulmonary diseases (AECOPD) or 15 healthy with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…We introduced clinical phenomics into trans-omics to evaluate network nodules cross lipidomic and phenomic layers and define phenome-specific lipid panels and lipid-specific phenome groups in acute lung injury patients with or without infections and with or without chronic diseases, as well as in patients with lung cancer subtypes. 8,15,17 To gather our present and previous studies, we found that the variation of trans-omic profiles in patients was TA B L E 8 Lipid elements significantly elevated or declined alone in lung cancer patients survived or nonsurvived (more than twofold), respectively, as compared with healthy control (P-values) more obvious, uncontrolled, and irregular due to the complex and comprehensive influencing factors in clinical practice and measurements. We also found that the integrated panel appeared lung cancer subtype-specific network and the construction to show statistical correlations and mechanistic molecular interactions between lipid metabolisms and phenome appearances in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We introduced clinical phenomics into trans-omics to evaluate network nodules cross lipidomic and phenomic layers and define phenome-specific lipid panels and lipid-specific phenome groups in acute lung injury patients with or without infections and with or without chronic diseases, as well as in patients with lung cancer subtypes. 8,15,17 To gather our present and previous studies, we found that the variation of trans-omic profiles in patients was TA B L E 8 Lipid elements significantly elevated or declined alone in lung cancer patients survived or nonsurvived (more than twofold), respectively, as compared with healthy control (P-values) more obvious, uncontrolled, and irregular due to the complex and comprehensive influencing factors in clinical practice and measurements. We also found that the integrated panel appeared lung cancer subtype-specific network and the construction to show statistical correlations and mechanistic molecular interactions between lipid metabolisms and phenome appearances in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 91%
“…[19][20][21][22] Clinical phenomes were furthermore integrated with lipidomic profiles in patients with pulmonary embolism, acute pneumonia, and acute exacerbation of chronic obstructive pulmonary diseases, based on clinical trans-omics principle. 15 Lipidomic profiles difference between health and lung cancer has been defined and it depends upon methodologies of measurement and analysis, sample preparations and sources, and patient populations and status. 8 For example, serum levels of lysoPC (C26:0 and C26:1) and PC (C42:4 and C34:4) were different between stage I NSCLC and healthy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipidomics has also been utilized to identify lipid profile differences between healthy and diseased human patients. For example, blood plasma from patients with diseases, such as acute lung infections, pulmonary embolism, or acute exacerbation of the chronic pulmonary disease, had a more than 2-fold increase in various lipids compared to healthy patients (109). Lipidomics and liquid chromatography-mass spectrometry may be used to diagnose subclinical coronary artery disease (110) determined that patients with severe coronary calcification tended to have greater levels of monounsaturated triacylglycerols and saturated triacylglycerols.…”
Section: Lipidomic Techniques and Applicationsmentioning
confidence: 99%
“…Despite improvements in clinical management, mortality remains high and there is no specific treatment, nor are there universally agreed-upon biomarkers for survival and outcome in ARDS. Different types of acute lung diseases have distinct lipid profiles (73) and lipid mediators may represent useful prognostic markers in critically ill patients. LTB4 correlates with lung-injury severity and outcome in patients with ARDS (64,65) and higher pro-inflammatory mediators like PGF2a and selected pro-resolving mediators like 10S,17S-diHDHA were predictive of ARDS development in patients with sepsis (61).…”
Section: Acute Respiratory Distress Syndrome (Ards)mentioning
confidence: 99%